2022
DOI: 10.1002/jgc4.1582
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors that influence genetic counselors’ decisions to refer patients to mental health providers

Abstract: Genetic counselors (GC) serve patients who are often in distress at the time of their consultation. GC competency includes providing short‐term, client‐centered counseling, while using community resources, such as mental health providers (MHPs), for psychosocial support. The purpose of this study was to assess the mental health referral practices of GCs; specifically, the rate of referrals, factors influencing a GC’s decision to refer, and barriers to referrals. GCs working in direct patient care for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, there are currently no training methods or guidelines for when genetic counselors should make referrals to mental health services, or how to discuss MHTP with patients (Hayes et al, 2022). Over half of those who responded, reported that they "sometimes" discussed MHTP with their patients suggesting Australian genetic counselors feel comfortable addressing the topic of psychiatric disorders in the context of accessing longterm psychological support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are currently no training methods or guidelines for when genetic counselors should make referrals to mental health services, or how to discuss MHTP with patients (Hayes et al, 2022). Over half of those who responded, reported that they "sometimes" discussed MHTP with their patients suggesting Australian genetic counselors feel comfortable addressing the topic of psychiatric disorders in the context of accessing longterm psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…It is within the scope of genetic counselors practice to be able to identify patients who could benefit from long‐term psychological support, and identify patients who may benefit from an Australian Government Mental Health Treatment Plan (MHTP). However, there are currently no training methods or guidelines for when genetic counselors should make referrals to mental health services, or how to discuss MHTP with patients (Hayes et al, 2022). Over half of those who responded, reported that they “sometimes” discussed MHTP with their patients suggesting Australian genetic counselors feel comfortable addressing the topic of psychiatric disorders in the context of accessing long‐term psychological support.…”
Section: Discussionmentioning
confidence: 99%